Digitalisasi Pelaporan Realisasi Penggunaan Anggaran Penanggulangan Kemiskinan Kota Palembang - faradillah; Fadhiel Alie, Muhammad; Rahmanda Putra, Rian (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
Poverty reduction is indeed a big task for countries around the world, including Indonesia. Poverty reduction programmes are often vulnerable to abuse due to various factors, such as a lack of transparency, accountability, and effective supervision. This research digitises reporting on the realisation of the use of the poverty reduction budget based on the web through the application of a geographic information system that shows maps of aid recipients, welfare conditions, and absorption of funds in poverty reduction programmes and activities in Palembang City through the development of a comprehensive Poverty Data Information System (SIDAK) using software. Development life cycle in system development methods. This SIDAK development uses DTKS (Integrated Social Welfare Data), which was previously called the Integrated Data Base (BDT), submission of budget and poverty reduction programme data from all OPDs in Palembang City as a data source in accordance with the nomenclature of programmes, activities, and sub-activities in this part of the design, referring to Minister of Home Affairs Regulation No. 90 of 2019.